Massive post-partum haemorrhage in a SARS-CoV-2 positive primi gravid patient: a case report - Ushna Ahmed; Nida Najmi; Rozilla Sadia Khan (Journal of the Pakistan Medical Association, 2023)
A 20-year-old, primi gravid, south Asian woman, was referred from secondary care to Aga Khan University Hospital for further management of primary post-partum haemorrhage after a normal vaginal delivery, on July 12, 2021. She was otherwise healthy, with no known comorbidity. She tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during her admission, on account of universal Covid-19 testing policy. Initially, conservative measures were instituted to control bleeding, including bilateral internal iliac artery ligation, concluding with hysterectomy to stop the haemorrhage. Multiple units of blood products had to be transfused. Obstetrical haemorrhage being the menace in this case, the possibility of Covid-19 positive obstetrics patients being more susceptible to massive post-partum haemorrhage, requiring more radical life-saving procedures to be conducted earlier, was considered. In future, more observational studies will be needed to determine any association between Covid-19 infection and obstetric haemorrhage. Keywords: Pregnancy, Covid-19, haemorrhage.